Persepsi Mahasiswa Prodi Ekonomi Syariah Sekolah Tinggi Agama Islam (STAI) Sangatta dalam Kemudahan Penggunaan Quick Response Code Indonesian Standard (QRIS) - Mohammad Rizki Ramadhan; Imrona Hayati; Ajis Supangat (Ekonomi Keuangan Syariah dan Akuntansi Pajak, 2026)
The development of information technology has driven the transformation of payment systems from conventional methods to digital payments, one of which is through the Indonesian Standard Quick Response Code (QRIS). This study aims to determine the perceptions of students in the Sharia Economics Study Program at Sekolah Tinggi Agama Islam Sangatta (STAI) regarding the ease of using QRIS. This study uses a qualitative approach with field research. Data were obtained through interviews, observations, and documentation of 20 students as informants. Data analysis techniques were carried out through data condensation, data reduction, data presentation, and verification, with validity testing using triangulation. The results showed that students had a positive perception of the ease of using QRIS. At the stimulus acceptance stage, the majority of students were able to accept and understand information about QRIS well. At the comprehension stage, students understood the steps for using QRIS and had used it in their daily transaction activities. At the evaluation stage, students expressed satisfaction because QRIS was considered easy, fast, and practical, even though there were still technical obstacles such as internet network disruptions. Overall, this study concluded that QRIS was perceived as an easy, efficient payment method that suited students' needs in conducting digital transactions.